1984
DOI: 10.1111/j.1365-2230.1984.tb00841.x
|View full text |Cite
|
Sign up to set email alerts
|

13-cis-retinoic acid for dyskeratinizing diseases-clinicopathological responses

Abstract: Summary Fifteen patients with Darier's disease (five patients), epidermolytic hyperkeratosis (five patients), and pityriasis rubra pilaris (five patients) were treated with doses ranging from 1.0 to 3.0 mg per kg body weight of 13 ‐cis retinoic acid. There was marked clinical improvement in the patients with Darier's disease which was sustained in two out of five on stopping treatment after 6 months. Three patients with pityriasis rubra pilaris went into remission, and required no further treatment on stopping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
5
0
4
Order By: Relevance
“…Overall, 743 records were identified and 182 studies were considered eligible for analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 743 records were identified and 182 studies were considered eligible for analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of retinoids in the treatment of PRP points to the probable role of vitamin A metabolism. [32][33][34][35][36][37][38][39][40] Rothman 41 observed that systemic vitamin A or its topical administration was a beneficial adjunct in follicular and /or nonfollicular hyperkeratosis of PRP. The widely reported association of PRP with autoimmune disorders may point to a probable underlying immunologic abnormality.…”
Section: Etiologymentioning
confidence: 99%
“…The synthetic retinoids have largely supplanted vitamin A therapy. Numerous reports appear in the literature of successful treatment with isotretinoin 20 , 21 , 114–120 . In 1976, Peck and Yoder 114 reported the successful treatment of a PRP patient with a 15‐week course of isotretinoin given at a maximum dose of 2.2 mg/kg/day.…”
Section: Treatmentmentioning
confidence: 99%